ANALYSIS OF DEIXIS IN THE STORY SELECTED FROM CHRISTIAN BIBLE, GENESIS - Sisilia Viona Anugrah (IKIP Siliwangi, 2018)
Language is more than a sign as it can function as a tool for communication among humans. This means that language can be learned by the humans. One of the fields that study the language is pragmatics. Pragmatics can be defined as the study of contextual meaning; therefore there should be a relationship between language and the context. However, this relationship can be recognized through deixis. The purpose of this paper is to analyze the types of deixis found in Chistian Bible, Genesis chapter 6, 7, 8, 9, 10. This paper uses descriptive qualitative method, because it analyzes the types of deixis found in this novel. The method of collecting the data is documentation. The deixis that mostly used in this bible is the person deixis with the frequency of 192 (39.91%). The following deixis is place deixis that appears 103 times (21.41%). The social deixis appears with the frequency of 83 (17.25%) while the time deixis appears with the frequency of 66 (13.72%). The final deixis that appears is discourse deixis with the frequency of 36 (7.69%). Keywords: Deixis, Bible, Genesis